Examining the selectivity of borohydride for carbon dioxide and bicarbonate reduction in protic conditions. (15th June 2015) - Grice, Kyle A.; Groenenboom, Mitchell C.; Manuel, John David A.; Sovereign, Mark A.; Keith, John A.
Abstract : Graphical abstract: Highlights: Borohydride reduces CO2 and bicarbonate to formate in purely aqueous solution. NMR and 13 C-labeling characterized reaction intermediates and products. First principles quantum chemistry was used to determine reaction energies. Hydricities of borohydrides in aqueous solution were calculated. Abstract: Sodium borohydride (NaBH4 ) reacts with carbon dioxide (CO2 ) and bicarbonate (HCO3 − ) in aqueous solution to produce formate (HCO2 − ). Isotopic labeling experiments verified the product identity and illustrated that the carbon in the product originated from CO2 /HCO3 − . The addition of CO2 to borohydride resulted in formate production in isopropanol as well. Accurate first-principles quantum chemistry was used to examine reaction energies and the hydricities of various borohydrides in aqueous solution. CO2 reduction is proposed to proceed through hydride transfer from BH4 − or from BH4− n (OH) n − ( n = 0–3) to CO2 and bicarbonate. The reaction energies were found to be competitive with those for hydrolysis of borohydride. These findings lay the foundation for the further development of systems for the catalytic conversion of CO2 and bicarbonate into fuels via hydride transfers in water.